La terminación de la unión de hecho no declarada frente a los derechos del ex conviviente. - Guambuguete Guambuguete, Nathaly Eugenia (2024)
This research work is of great importance, since in our Ecuadorian legislation the constitutive elements of the Union of Fact are detailed and protect the rights of the cohabitants only when it is recognized, but there is a violation when the declaration is not made effective by the cohabitants, and this, due to the fact that when a separation is generated, there will be a loss for either of the spouses since, since it is not recognized, they will not be able to claim the assets that were produced within the company. The reduction in marriages and the increase in de facto unions, or also known as free unions in Ecuador, deserve a precise analysis, since the de facto union is considered a civil state and generates the same effects, rights and obligations that creates a marriage. The problem arises when the people who live in a de facto union want to access the benefits, rights, duties and obligations that the spouses have and that this be recognized and registered in the Civil Registry, or when they want to end the union of fact, since most of these unions are not registered. The work method that will be used in the following research will be qualitative and quantitative, which is made up of techniques, methods and tools for formulating the problem, objectives, hypotheses, variables and certain identification tools for collecting information; which will be tabulated, processed and analyzed through reasoning techniques and proportions, supported by the Theoretical Framework, Methodological Framework as well as the technique of Evaluation of Results that will be obtained within the conclusions and recommendations of the surveys expressed to the professionals of the Law, and other people so that the line of inquiry in which this investigation is framed is that of Administration of Justice. 4 KEYWORDS: De facto union, cohabitants, separation, infringement.